Characteristics of H2S at low adsorption temperature using nitrogen-enhanced carbon modified with Ni nanoparticles / Norfazilah Abdullah and Norhusna Mohamad Nor - Abdullah, Norfazilah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
The main objective of this research is to investigate the adsorption characteristics of palm shell activated carbon (PSAC) adsorbent impregnated with nickel nanoparticles (Ni nps) and urea (Ni-N-PSAC) towards hydrogen sulfide (H2S) gas removal at low adsorption temperature (30°C). The impregnation of Ni nps is expected to enhance the oxygen functional groups onto the adsorbent’s structure, whereas the impregnation of urea will contribute to tailoring the nitrogen functional groups. It is expected that the Ni-N-PSAC adsorbent will exhibit heightened efficiency in removing H2S at low adsorption temperature conditions. The H2S adsorption was tested at various operating conditions such as different feed flowrate (100 – 250 ml/min), relative humidity, %RH (0 – 80 %RH) and H2S feed concentrations (1000 – 4000 ppm). The adsorption characteristics of H2S onto Ni-N-PSAC adsorbent were analyzed using adsorption isotherms and kinetics studies. The highest H2S adsorption capacity calculated was 114.66 mg H2S/g Ni-N-PSAC, where the adsorption parameters were at 100 ml/min, 30°C, 1000 ppm H2S and 40 %RH. The removal of H2S at low temperatures using Ni-N-PSAC showed that Temkin isotherm represents the best adsorption characteristics with R2 = 0.9653. The kinetic study suggests that Pseudo second-order yields the most favourable result (R2 = 0.9967). The outcome of this work is expected to provide new knowledge on the adsorption characteristics of H2S using Ni-N-PSAC adsorbent at low adsorption temperature (30°C).